2022
DOI: 10.17221/357/2022-pse
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of selenium biofortification of spring wheat: the role of soil properties and organic matter amendment

Abstract: The effect of soil selenate application to two different soils (Phaeozem and Cambisol) on biomass yield and selenium (Se) uptake by spring wheat (Triticum aestivum L.) was investigated in a pot experiment. Additionally, organic amendment (fugate, i.e. liquid by-product from the biogas plant) was applied to assess (i) the effect of organic matter on the bioavailability of Se and (ii) the fugate (containing 2.3 mg/kg of Se) as a potential source of Se for plants. Selenium was applied at two levels: 6.4 µg/kg (Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Mrstina et al . (2022) also reported that the selenium content in wheat reached 455 μg kg −1 . More important than that, there is an urgent need to turn these positive results into the end‐use products consumed frequently by society.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Mrstina et al . (2022) also reported that the selenium content in wheat reached 455 μg kg −1 . More important than that, there is an urgent need to turn these positive results into the end‐use products consumed frequently by society.…”
Section: Introductionmentioning
confidence: 93%
“…Kiran et al (2021) stated that the zinc concentration in the bread wheat grain increased by 170% with the foliar application of zinc in three different plant growth periods. Mrstina et al (2022) also reported that the selenium content in wheat reached 455 lg kg À1 . More important than that, there is an urgent need to turn these positive results into the end-use products consumed frequently by society.…”
Section: Introductionmentioning
confidence: 95%
“…In this section, we initially summarize the crucial role of Se fertilizer strategies, including how to adjust the type [36][37][38] and dosage of Se fertilizers [39,40], and the application site [32,41] and timing of Se [42,43]. Subsequently, we consolidate and discuss the impacts of agronomic management strategies on Se biofortification, encompassing crop rotation [44][45][46] and intercropping [47][48][49] and soil [50][51][52] and water management [53][54][55], as well as microbial inoculation [56][57][58]. As the most accessible methods for farmers, agronomic strategies play an irreplaceable role in Se biofortification practices.…”
Section: Agronomic Strategies For Se Biofortificationmentioning
confidence: 99%
“…The selenium compounds, Na 2 SeO 4 and Na 2 SeO 3 , are most commonly used in conventional fertilizers, as they are more economical than organic Se fertilizers ( Broadley et al., 2006 ; Broadley et al., 2010 ). However, the availability of Se to plants from the soil is highly dependent on physicochemical properties, such as pH and redox potential of soil, chemical speciation, and the activity of soil microorganisms ( Lyons, 2010 ; Mrština et al., 2022 ). All these soil-related factors render the Se applied fertilizer less plant-available under prevailing field conditions ( Schiavon and Vecchia, 2017 ), thus foliar application of Se salts may be the best option for lowering the risk of Se immobilization in the soil.…”
Section: Introductionmentioning
confidence: 99%